TOURIST POTENTIAL OF THE REGION AS A FACTOR VOLOGDA DEVELOPMENT OF INTERREGIONAL COOPERATION IN TOURISM - M. Andreeva; I. Krukova (Вестник университета)
The possibility and expediency of active participation of the Vologda region in various forms of interregional cooperation in the field of tourism is substantiated in the article, since it will allow to use the tourist potential of the region more fully. The authors proposed such a low-cost and effective instrument of cooperation as a single calendar of events in tourism on the territory of the North-West Federal District.